Skill Building for Teachers at a Chinese Special Needs School through International Videophone Teleconsultation: Helping Teachers Develop and Improve Choice-making in Students with Intellectual Disabilities. Issue 5 (3rd September 2022) - Pei, Hong; Sonoyama, Shigeki
ABSTRACT: In cooperation with a special needs school in China, we conducted an international consultation by videoconference to improve the support system for developing the choice-making that young students with intellectual disabilities exhibit in school settings. Based on an assessment of these young students' choice-making, we examined the (1) methods to support the development of choice-making (as a behaviour chain in which a child chooses and then engages in an activity, (2) significance of such support, and (3) usefulness of videophone teleconsultation. This helped us develop and improve the students' choice-making and refine the teachers' techniques for developing choice-making in students with intellectual disabilities. This suggests that videophone teleconsultation is an effective means of supporting the development of the choice-making of students with intellectual disabilities in school situations. Furthermore, there is a need to examine the use of videophone teleconsultation in school activities in general.